PENGEMBANGAN KOMPETENSI GURU DALAM RANGKA PENINGKATAN KUALITAS PENDIDIKAN DI SMK NEGERI 3 MANADO - Phebe Silvanna Londok; Agus Wahono (MAP (Jurnal Manajemen dan Administrasi Publik), 2018)
This study aims to highlight the development of teacher competence to improve the quality of education in SMK Negeri 3 Manado. In addition, also to describe and analyze the efforts of teacher competence development to improve the quality of education in SMK Negeri 3 Manado. Furthermore, to know and analyze the factors driving / inhibiting efforts to develop teacher competence to improve the quality of education in SMK Negeri 3 Manado. The type of this research is descriptive qualitative, done by describing in words and language, as a form to know the steps in developing personal competence of teacher working at SMK Negeri 3 Manado by using method of interview, observation and documentation. The results show that the competence of existing teachers is good, but still need to be improved and developed in accordance with the demands of the times because science and technology continue to grow. Keywords: teacher competence, quality of education